1981
DOI: 10.1212/wnl.31.7.819
|View full text |Cite
|
Sign up to set email alerts
|

Primary systemic carnitine dehciency. II. Renal handling of carnitine

Abstract: Renal tubular reabsorption rates, reabsorptive maxima, and apparent renal plasma excretory thresholds for carnitine were determined in four children with primary systemic carnitine deficiency (SCD), in two of the mothers of these children, in one patient with muscle carnitine deficiency (MCD), and in seven controls. In SCD the observed values were well below those found in six of seven controls, but one control, a healthy 20-year-old woman with normal muscle carnitine level, also exhibited a renal carnitine le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
2
4

Year Published

1984
1984
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 145 publications
(54 citation statements)
references
References 0 publications
5
43
2
4
Order By: Relevance
“…Because the normal mean fractional excretion of free carnitine is only 1-2%, the method tends to overestimate the threshold. This may partly account for fact that the value of 56 pmol/L found in the control child was considerably higher than the value of 35-40 pmol/L found in normal subjects by Engel et al (12) using carnitine loading. Moreover, as noted above, the effects of prior carnitine treatment had not disappeared completely in this child by the end of the study period.…”
Section: Resultscontrasting
confidence: 57%
See 3 more Smart Citations
“…Because the normal mean fractional excretion of free carnitine is only 1-2%, the method tends to overestimate the threshold. This may partly account for fact that the value of 56 pmol/L found in the control child was considerably higher than the value of 35-40 pmol/L found in normal subjects by Engel et al (12) using carnitine loading. Moreover, as noted above, the effects of prior carnitine treatment had not disappeared completely in this child by the end of the study period.…”
Section: Resultscontrasting
confidence: 57%
“…The MCAD, IVA, and PA patients had estimated renal thresholds for free carnitine between 10 and 25 pmol/L, well below either that of the control child or the range found by the carnitine infusion method. In both of the LCAD patients, the estimated renal thresholds for free carnitine were lower than that of the control child but not below those reported by Engel et al (12). There was no evidence of other renal tubular dysfunction such as glucosuria or phosphate or bicarbonate wasting in any of the patients, and in vitro studies have shown that the carnitine transport system is normal in MCAD and LCAD (9).…”
Section: Resultscontrasting
confidence: 46%
See 2 more Smart Citations
“…However, during the first month of hemodialysis therapy, plasma L-carnitine concentrations declined by approximately 30%, and after 12 months they had decreased by approximately 40%, with a pattern suggesting an ongoing decline (12 L-carnitine is not bound to plasma proteins and therefore is freely filtered at the Glomerulus (13). However, at plasma concentrations greater than approximately 60 mmol/L, fractional reabsorption begins to decrease because of partial saturation of the tubular transporter (14).…”
Section: Discussionmentioning
confidence: 99%